Orchestrating Educational Innovation in the Digital Era: A Literature Review on School Implementation Strategies and Challenges - Muhammad Aprizal; Nursalimah Nursalimah; Dismawati Dismawati; Riska Meisyi Putri; Muhammad Ali Basroh; Retno Wahyu Ningsih (Universitas Nurul Jadid Probolinggo, Indonesia, 2025)
Digital transformation has fundamentally reshaped educational systems, requiring schools to adopt effective innovation management practices to improve learning quality and institutional performance. This study aims to analyze educational innovation management in the context of digital transformation by examining implementation strategies, identifying the factors supporting successful innovation, exploring barriers encountered by schools, and synthesizing effective management practices based on recent research. The study employed a qualitative approach using a Systematic Literature Review (SLR). Relevant articles published between 2022 and 2026 were systematically collected from Google Scholar and Garuda databases and analyzed through content analysis. The findings reveal that successful educational innovation management depends on integrating top-down policy direction with bottom-up stakeholder participation, supported by strategic planning, innovative leadership, teacher digital competence, technological infrastructure, and organizational collaboration. However, the implementation process continues to face challenges, including limited digital competencies, inadequate technological infrastructure, resistance to organizational change, and financial constraints. The study implies that effective educational innovation management requires a balanced combination of policy support, institutional capacity, and stakeholder engagement to establish adaptive, sustainable, and high-quality educational systems capable of responding to the demands of continuous digital transformation.